1989
DOI: 10.1007/bf00051496
|View full text |Cite
|
Sign up to set email alerts
|

Particulate sulfate levels at a rural site in Israel

Abstract: Ambient particulate sulfate measurements have been intermittently performed at a rural site in Israel over a period of more than two years. Concurrent measurements of ambient pollutants (SO2, NO-NOx, and 03), as well as meteorological data, were also carried out. The daily data included four particulate sulfate samples representing four successive 6 h accumulating periods. The measured concentrations of sulfate ions ranged from a low 2 lag m -3 observed during the winter season to a high of > 50 lag m -3 obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…As previously reported [Luria et al, 1989a] SO42-measured in Etzion during the period 1984-1986 showed a diurnal distribution with peak levels during the third time segment (1200-1800). Consistently higher values were also observed in the Jerusalem 1987Jerusalem -1988 data.…”
Section: The Diurnal Cyclesupporting
confidence: 81%
See 1 more Smart Citation
“…As previously reported [Luria et al, 1989a] SO42-measured in Etzion during the period 1984-1986 showed a diurnal distribution with peak levels during the third time segment (1200-1800). Consistently higher values were also observed in the Jerusalem 1987Jerusalem -1988 data.…”
Section: The Diurnal Cyclesupporting
confidence: 81%
“…The seasonal variability of particulate sulfate in Israel was first reported in an earlier publication [Luria et al, 1989b], based on the 1984-1986 measurements. A more detailed annual cycle is shown in Figure 19 which shows a 21-point running average of the 1988 measurements.…”
Section: Seasonal Variabilitymentioning
confidence: 96%
“…Some of this anomaly can be explained by biogenic generation of marine dimethylsulphide which is emitted into the atmosphere and transformed into sulphate containing compounds (Ganor et al, 2000b) and some by industrial activity along Israel's coastline, but most of it is attributed to long-range transport of sulphur containing air masses from Europe (Foner and Ganor, 1992;Ganor et al, 1993;Levin et al, 1990;Luria et al, 1989Luria et al, , 1996Mamane and Gottlieb, 1995;Singer et al, 1993;Singer, 1994;Sobanska et al, 2003). These anomalous sulphate levels have been found in air masses from as far south as the Negev Desert (Sobanska et al, 2003) to as far north as the vicinity of Damascus, Syria, approximately 100 km NE of Lake Kinneret (Cornille et al, 1990).…”
Section: Constituentmentioning
confidence: 99%
“…PM concentrations in urban areas such as the coastal city of Tel Aviv are even higher due to anthropogenic SO 4 locally produced or transported from Europe (Foner and Ganor, 1992). Rural locations in Israel have also been impacted by the advection of SO 4 particles originating from Europe (Luria et al, 1989).…”
Section: Israel and Taiwanmentioning
confidence: 99%